Bacteriological Quality of Farmed Freshwater Fish and Shellfish Meant for Export - J.R., Bandekar; A.S., Kamat; M., Karani; V., Dhokane; R., Shashidhar; A., Kakatkar; N., Ghadge; A., Bhat; V., Venugopal; S.B., Warrier (Fishery Technology, 2025)
Bacteriological screening of 48 samples comprising of 12 samples of headless and 6 samples of whole prawn (Macrobrachium rosenbergii), 24 samples of processed rohu and 6 samples of whole rohu (Labeo rohita) obtained from fish processing factories of Kakinada and Mumbai were screened for aerobic plate count (APC) and for pathogens including Salmonella sp., Vibrio cholerae, Escherichia coli, Staphylococcus aureus and Listeria monocytogenes. The samples of processed rohu (steak) obtained in four different batches (18, samples) were of good bacteriological quality. The APC was 20 cfu/g). However, no other pathogens were detected in any of the samples. APC was > 105 cfu/g in 33% of whole rohu samples obtained from Kakinada. Â£. coli (